1984
DOI: 10.1002/ajpa.1330640309
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic studies in three Chinese minorities

Abstract: Three minority ethnic groups from China (Mongolians, Koreans, Zhuang) were examined with respect to the genetic markers GLO, GPT, ACP, ESD, 6-PGD, PGM1 subtypes, C3, and TF. Significant variations were noted for the gene frequencies of GLO, GPT, ESD, sub PGM1 between Zhuang and Mongolians; for GPT, ACP, ESD, sub PGM1 between Zhuang and Koreans; and for GLO between Mongolians and Koreans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…C3*F frequencies vary from 0 to .017, which is very low, but characteristic for Mongoloid populations, in which C3*F frequencies between 0 and .06 have been observed. Zhao (1983) found .004 in Chinese from Shanghai, whereas the corresponding values varied from .002 to .012 in three Chinese minorities (Mongolians, Koreans, and Zhuang), as reported by Goedde et al (1984). The rare allele C3*S0.25, which was observed by these investigators in Mongolians and Koreans (frequencies .005 and .003, respectively), could not be found in our population sample.…”
Section: ---contrasting
confidence: 44%
“…C3*F frequencies vary from 0 to .017, which is very low, but characteristic for Mongoloid populations, in which C3*F frequencies between 0 and .06 have been observed. Zhao (1983) found .004 in Chinese from Shanghai, whereas the corresponding values varied from .002 to .012 in three Chinese minorities (Mongolians, Koreans, and Zhuang), as reported by Goedde et al (1984). The rare allele C3*S0.25, which was observed by these investigators in Mongolians and Koreans (frequencies .005 and .003, respectively), could not be found in our population sample.…”
Section: ---contrasting
confidence: 44%
“…The sources of some additional data were as follows: GPT (Ueda et al, 1979) and ESD (Omoto et al, 1975). The data on blood genetic markers of Koreans were taken from Yuan et al (1984) and Goedde et al (1984). The data on other populations were obtained from Roychoudhury and Nei (1988) and Masatoshi Nei (personal communication), with the exception of our unpublished data on two Negrito populations of the Philippines.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Goedde et al [1984] reported the distribution of gene frequencies of PGM1 subtypes in three Chinese minori ties, Mongolians, Koreans and Zhuang. Significant differences between Zhuang and Mongolians or Koreans were shown.…”
Section: Methodsmentioning
confidence: 99%